Socio-demographic factors, food security and mental health status among mothers in Mentakab, Pahang, Malaysia - Mamat, Noratikah; Sulaiman, Norhasmah; Mesbah, Siti Farhana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Women are vulnerable to food insecurity. This study aimed to determine the demographic factors, food security and mental health status among mothers in Mentakab, Pahang. Methods: This cross-sectional study was participated by 129 mothers aged 20 years to 59 years old. Mothers were interviewed to obtain information on demographic factors, food security status (Radimer/Cornell Hunger Scale) and mental health status (DASS-21). Chi-square and binary logistic regression were used to determine an association between factors and food security status. General linear model (GLM) was used to determine the difference in mental health score according to food security status group after controlling for covariates. Significance level was set at 0.05. Results: The mother’s mean age was 38.30 ± 9.70 years. Prevalence of food insecurity was 55.8%. About 39.5% of mothers were depressed, 24.0% were experienced anxiety and 16.3% of mothers were stressed. The mean depression and anxiety score were 4.11 ± 3.54 and 2.96 ± 3.19 respectively. The mean stress score was 3.91 ± 3.44. Low household income (p<0.01) was increased the risk of food insecurity by nine fold. After controlling the covariates, there was significant difference in mean of depression score (p<0.01), anxiety score (p<0.01) and stress score (p<0.01) based on the food security status. Conclusion: More than half of the households were food insecure. Low household income was a main contributor towards food insecurity. Poor mental health status was associated with food insecurity. Lifestyle management and skills equipment need to arrange for mothers to improve their mental health status and socio-economic status.